2015
DOI: 10.1111/tpj.12789
|View full text |Cite
|
Sign up to set email alerts
|

Symbiodinium transcriptome and global responses of cells to immediate changes in light intensity when grown under autotrophic or mixotrophic conditions

Abstract: SummarySymbiosis between unicellular dinoflagellates (genus Symbiodinium) and their cnidarian hosts (e.g. corals, sea anemones) is the foundation of coral reef ecosystems. Dysfunction of this symbiosis under changing environmental conditions has led to global reef decline. Little information is known about Symbiodinium gene expression and mechanisms by which light impacts host–symbiont associations. To address these issues, we generated a transcriptome from axenic Symbiodinium strain SSB01. Here we report feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 79 publications
(85 reference statements)
8
96
1
Order By: Relevance
“…Overall, the differences in levels of transcript accumulation that we observed were small, consistent with previous studies of gene-expression changes in SSB01 during exposure to different light intensities (Xiang et al, 2015). Only six transcripts exhibited a change in abundance of .10-fold at any time point following transfer to IMK+Glc medium (in either the light or the dark) but not when transferred to IMK medium (Supplemental Table S3).…”
Section: Changes In Gene Expression During Growth In the Presence Of Glcsupporting
confidence: 90%
See 2 more Smart Citations
“…Overall, the differences in levels of transcript accumulation that we observed were small, consistent with previous studies of gene-expression changes in SSB01 during exposure to different light intensities (Xiang et al, 2015). Only six transcripts exhibited a change in abundance of .10-fold at any time point following transfer to IMK+Glc medium (in either the light or the dark) but not when transferred to IMK medium (Supplemental Table S3).…”
Section: Changes In Gene Expression During Growth In the Presence Of Glcsupporting
confidence: 90%
“…Although this scoring is somewhat subjective, it was consistent in replicate trials in which individual images were scored without the observer's knowing in which medium the cells had been grown. A similar difference in surface structure was observed previously by SEM of cells grown in high light (typically more rough and convoluted) relative to cells grown in low light or maintained in the dark (typically smoother; Xiang et al, 2015). Differences in surface structures were also observed by TEM.…”
Section: And E)supporting
confidence: 82%
See 1 more Smart Citation
“…While most of the studies on SOD and CAT enzymes in Symbiodinium suggested these enzymes play a major role in coping with an increase of sea temperature to prevent coral bleaching [91][92][93], a number of studies in other organisms revealed that these enzymes may act in response to other types of environmental stress such as salinity, exposure to hydrogen peroxide and drought conditions [94][95][96]. Apart from the antioxidative response, cell adhesion proteins also play a role in maintaining coral-Symbiodinium symbiosis interaction [9]. Genes encoding for cell surface molecules such as Sushi, Von Willebrand factor type A, EGF and pentraxin domain containing 1 (Svep1) were downregulated during the event of induced bleaching in their coral host.…”
Section: Symbiosismentioning
confidence: 99%
“…Dinoflagellates are found in a range of marine ecosystems including estuaries, mangroves and deep-sea environments, and some exist as symbionts with other organism such as coral and epiphytes of seaweeds and seagrass [2][3][4][5][6]. Their lifestyle ranges from mixotrophic through to heterotrophic and autotrophic [7][8][9]. They also have been reported to be the major cause of the harmful algae blooms (HABs), sometimes referred to as 'red tide' events in the ocean, and may result in death of marine mammals and affect human health due to the accumulative effect of toxins moving throughout the food chain when contaminated seafood is consumed [10,11].…”
Section: Introductionmentioning
confidence: 99%